If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 16 = 20 + 17 Reorder the terms: 16 + X = 20 + 17 Combine like terms: 20 + 17 = 37 16 + X = 37 Solving 16 + X = 37 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + X = 37 + -16 Combine like terms: 16 + -16 = 0 0 + X = 37 + -16 X = 37 + -16 Combine like terms: 37 + -16 = 21 X = 21 Simplifying X = 21
| -2(2t+1)=2 | | 48+x=47+31 | | .4w+60=1w+53 | | 9-8m=17 | | (x^2)-4x=6 | | 7m+1-1=4m+6m | | -3x+6x+24=9 | | 4+x=7+2 | | .4w+60=e+53 | | r+2r+3r=4 | | 4(f-8)=-16 | | 10m-21=79 | | V+15=7 | | 6z+3z=63 | | -3x+4=3 | | 8=8z | | 2000+.56x=545+73x | | -10(s+1)=63 | | 9w+4w=76+2 | | -(c-5)=0 | | 6y-14=40 | | 121y^2-3=31 | | 7w-6w=2 | | 15(t-2)=2t | | -[8x-(16x+4)]=4+(7x+3) | | (4+3x)(x+6)= | | x^3-3x^2-5x+15= | | -6=20h | | -3(2h-3)=29-h | | 14x+18x-9+5=-8x+5-9 | | 11z=16-3(10-4z) | | 9(x+2)+2=-6(x-6)-8 |